ALGAS CALCAREAS DE LA FORMACION ARROYO VERDE (EOCENO, PROVINCIA DEL CHUBUT, ARGENTINA). SISTEMÁTICA DE LOS PRINCIPALES GÉNEROS Y CONSIDERACIONES PALEOAMBIENTALES (Ameghiniana, 2013)
CALCAREOUS ALGAE FROM ARROYO VERDE FORMATION (EOCENE, CHUBUT PROVINCE, ARGENTINA).SYSTEMATIC DESCRIPTIONS OF THE MAIN GENERA AND PALAEOENVIRONMENTAL CONSIDERATIONS. Calcareous beds of the Arroyo Verde Formation (Eocene) have furnished an algal association belonging mainly to the orders Dasycladales, Caulerpales and Cryptonemiales. Based on paleoecological evidence, the habitat inferred for the described specimens correspond to shallow, subtropical, low-energy marine waters of normal salinity with a sand and mud substrate. This paper represents the first systematic study carried out in Argentina of an association of fossil calcareous algae.